2019
DOI: 10.21037/cco.2019.07.03
|View full text |Cite
|
Sign up to set email alerts
|

Management of gallbladder cancer in India

Abstract: Gallbladder cancer is a highly aggressive disease with variable prevalence across the globe.Particularly the Indo-Gangetic belt in Northern India has an incidence as high as 21/100,000. Majority of cases are detected either incidentally on pathological evaluation of cholecystectomy specimens or present with advanced disease. Radical surgery remains the mainstay of cure but only a small subset of patients is operable at presentation, and even with curative surgery recurrence rates remain high. Much debate surro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
70
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(76 citation statements)
references
References 58 publications
2
70
0
3
Order By: Relevance
“…Studies comparing FAPI and FDG PET/CT in the same cohort of primary gastric adenocarcinoma patients showed that all primary gastric tumors were FAPI positive (100% detection rate), but that only half of the tumors were FDG positive (50% detection rate) (49). In a study of 38 gastric cancer patients including 31 adenocarcinomas and seven signet-ring cell carcinomas, the sensitivities of 68 Ga-FAPI-04 PET/CT and 18 F-FDG PET/CT for the diagnosis of primary gastric cancer were 100% and 82%, respectively. Four cases of adenocarcinoma and three cases of signet-ring cell carcinoma were missed by 18 F-FDG PET/CT (4).…”
Section: Stomachmentioning
confidence: 99%
“…Studies comparing FAPI and FDG PET/CT in the same cohort of primary gastric adenocarcinoma patients showed that all primary gastric tumors were FAPI positive (100% detection rate), but that only half of the tumors were FDG positive (50% detection rate) (49). In a study of 38 gastric cancer patients including 31 adenocarcinomas and seven signet-ring cell carcinomas, the sensitivities of 68 Ga-FAPI-04 PET/CT and 18 F-FDG PET/CT for the diagnosis of primary gastric cancer were 100% and 82%, respectively. Four cases of adenocarcinoma and three cases of signet-ring cell carcinoma were missed by 18 F-FDG PET/CT (4).…”
Section: Stomachmentioning
confidence: 99%
“…Gallbladder cancer (GBC) is the most common cancer of the biliary tract system and ranked as the top six in general gastrointestinal tract neoplasms worldwide. 1 3 While the incidence rate of GBC varies widely, it has a unique distribution pattern in some regions, where Chile, India, some other Asian countries, Eastern European, and Latin American countries have reported more cases than the rest of the world every year. 4 6 This geographical distribution signature probably ascribed to the difference of genetic susceptibility contributes to an important risk factor of GBC.…”
Section: Introductionmentioning
confidence: 99%
“…El trabajo es muy relevante y se desarrolló muy bien debido a sus resultados estadísticos. Por supuesto, el artículo se relaciona con el diagnóstico de carcinoma incidental (estudio de patología), donde la literatura menciona que el carcinoma se encuentra entre el 0,2 %-1,1 % de todas las colecistectomías laparoscópicas (7).…”
unclassified
“…El CVB tiene una de las sobrevidas más cortas desde el momento del diagnóstico, lo que refleja su comportamiento agresivo y su diagnóstico tardío (7). Cabe destacar que solo 1 de 5 pacientes puede ser diagnosticado cuando la enfermedad está todavía localizada en la vesícula (1).…”
unclassified
See 1 more Smart Citation